Chronická pankreatitida jako rizikový faktor karcinomu pankreatu - Dítĕ, P; Pazourková, M; Růzicka, M; Precechtĕlová, M; Novotný, I; Dastych, M (Vnitrni lekarstvi, 2002)
Carcinoma of the pancreas is a very serious disease as regards early diagnosis, effective therapy and screening of the disease. Possible risk factors of development of carcinoma of the pancreas include chronic pancreatitis. In the submitted investigation the authors evaluated 213 patients under long-term (more than 5 years) dispensary care with the diagnosis of chronic pancreatitis. In these patients they proved unequivocally carcinoma of the pancreas on the background of chronic pancreatitis in 11 instances, incl. 71.8% where from the etiological aspect chronic alcoholic pancreatitis was involved. Practically all patients were smokers, incl. 8 who were regular smokers of more than 10 cigarettes per day for a number of years. Carcinoma of the pancreas is a serious disease, patients with long-term chronic pancreatitis are at risk (prevalence of carcinoma 5.1) and within the framework of dispensary care they must be systematically examined with regard to possible malignant growth on the background of chronic pancreatitis.
Keywords: Carcinoma; pankreatitida; nádory slinivky břišní; Humans; lidé středního věku; Chronic Disease; Female; rizikové faktory; dospělí; lidé; karcinom; Adult; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; chronická nemoc; Pancreatitis; mužské pohlaví; Risk Factors